Discount window stigma after the global financial crisis - Olivier Armantier; Marco Cipriani; Asani Sarkar (Federal Reserve Bank of New York, 2024)
We study Discount Window (DW) stigma, the reluctance to access the Federal Reserve's lender-of-last-resort facility, between 2014 and 2024. Despite increased usage since 2020, we find conclusive evidence that the DW is stigmatized, especially among smaller banks and when financial markets experience disruptions. In particular, evidence of DW stigma emerged months before the 2023 banking turmoil and had not subsided a year later. We also identify new determinants and consequences of DW stigma. The implications of these results for the provision of emergency liquidity are discussed.
Keywords: E52; G21; G28; 330; discount window; lender of last resort; stigma